Dampak Pandemi Covid-19 Terhadap Perekonomian Dalam Tinjauan Sektor Perdagangan Dan Pariwisata Kabupaten Nganjuk (Deskriptif Analisis Sektor Perdagangan) - Nik Haryanti; Dewi Fitrotus Sa’diyah; Diah Ismaya (Jurnal Dinamika Ekonomi Syariah, 2021)
At the end of 2019, the world was shocked by Covid-19 from China. Not only causing casualties but also having an impact on the national economy, including in Nganjuk Regency. To restore economic stability, the Nganjuk Regency Government took steps in implementing the new normal so that the community remained productive and maintained economic stability. The problem raised in this study is the economic growth of the people of Nganjuk district before and during the Covid-19 Pandemic and its impact on employment opportunities and household income of the Nganjuk community. The purpose of this study is to see the economic growth of the Nganjuk community before and during the Covid-19 Pandemic and its impact on employment opportunities and household income of the Nganjuk community. The type of research used in this research is descriptive research with a qualitative approach. The results show that the economic growth of the Nganjuk Regency community before the Covid-19 outbreak was felt to be stable, this can be seen from the income of traders which tends to increase. During the period past the Covid-19 pandemic, the community had a significant economic impact, this was felt by many traders who experienced a decrease in turnover of around 75%. And based on the central statistical agency, the number of unemployed people in 2019 has increased by 3 thousand people. To respond to the impact of the Covid-19 pandemic.